Conference Record of the 2004 IEEE International Symposium on Electrical Insulation
DOI: 10.1109/elinsl.2004.1380560
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental investigation results of diagnostic technique for deteriorated polymer insulators

Abstract: Polymer insulators are widely used aU over the world, owing to their excellent contamination performance, light weight, anti-vandalism characteristics, etc. Ageing deterioration is, however, inevitable with these insulators due to organic materials used for the weather shed and core, and mechanical andlor electrical breakdown ofthese insulators are a point of ongoing concern. Diagnostic methods to detect deteriorated polymer insulators are not established yet, although ClGRE SC 22 reported various techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Even so, insulator leakage current measurements in real-time applications depend not only on pollution deposits but also on environmental variables, which fluctuate over time [10,23]. Salam et al found that the leakage current increased as the wind speed increased in the range of 2-4 m s −1 [24] and other authors found that the leakage current increased when insulators lost their hydrophobicity [25][26][27][28][29]. Several studies have reported the relationship between leakage current and relative humidity [13,25,27], and others found that temperature changes had a minor effect on leakage currents [30].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, insulator leakage current measurements in real-time applications depend not only on pollution deposits but also on environmental variables, which fluctuate over time [10,23]. Salam et al found that the leakage current increased as the wind speed increased in the range of 2-4 m s −1 [24] and other authors found that the leakage current increased when insulators lost their hydrophobicity [25][26][27][28][29]. Several studies have reported the relationship between leakage current and relative humidity [13,25,27], and others found that temperature changes had a minor effect on leakage currents [30].…”
Section: Introductionmentioning
confidence: 99%
“…En niebla fría, la corriente de fuga aumenta en mayor proporción que en lluvia, dado que la tasa de humedecido es lenta y con mayor absorción en la deposición [73]. Otros estudios hallaron que la corriente de fuga aumentaba cuando los aisladores pierden su hidrofobicidad [68,69,[75][76][77].…”
Section: Monitorización Del Nivel De Depósitos De Contaminaciónunclassified